Quo vadis galaxy evolution?: a conference to reflect, and to chart the course of extragalactic astronomy - Wylezalek, Dominika; Bañados Torres, Eduardo (Nature astronomy, 2025)
A conference at the International Academic Forum of Heidelberg University, Germany, brought together 80 experts across various disciplines to recount recent breakthroughs in extragalactic astrophysics and ask, where are you going, galaxy evolution?
Online veröffentlicht: 27. August 2025
Gesehen am 17.12.2025